Does mesh utilization in femoral hernia repair affect recurrence? (Annals of Medical Research, 2021)
Aim: The mechanism of how femoral hernias (FH) develop is not clear. As a result of increased intra-abdominal pressure, preperitoneal fat tissue passes through the femoral ring and also drags the pelvic peritoneum.Femoral hernias are more common in women and also approximately 60% occur on the right, 30% on the left side and 10% are bilateral. The chief complaints of the patients are swelling and pain in the groin. Most cases require emergency operation due to incanceration or strangulation. Hernia repair can be performed with or without mesh, and with open or laparoscopic techniques.In this retrospective study, we aimed to compare the recurrence rates in patients who underwent FH repair with and without mesh.Material and Methods: This is a retrospective study of 48 patients who underwent surgery due to FH in our clinic between January 2012 and October 2017. The patients were divided into two groups according to mesh utilization: Hernia repair with mesh (Group 1) and hernia repair without mesh (Group 2).Results: A total of 48 patients with FH were operated (35 females, 13 males). The mean age of the patients was 64.6 ± 18.3 years and, 31 patients (64.5%) had right-sided and 17 patients (35.5%) had left-sided hernia.When the groups were compared, there was a statistically significant difference in terms of comorbidity, length of hospital stay and morbidity. There was no significant difference in recurrence (recurrence rates: 6.3%, 6.3%, respectively).Conclusion: Currently, mesh and non-mesh repairs are commonly used for the treatment of FH. This study showed that absence of mesh in FH repair did not affect recurrence.